Effects of a soluble dietary fibre NUTRIOSE® on colonic fermentation and excretion rates in rats - Guerin-Deremaux, Laetitia (The Korean Nutrition Society and the Korean Society of Community Nutrition, 2010)
The resistant dextrin NUTRIOSE®, developed from starch, is expected to act as a prebiotic. The aim of this study was to determine the effects of NUTRIOSE® on cecal parameters, short-chain fatty acid (SCFA) concentrations, and fecal excretion in rats. In an initial experiment, twenty-four male Fischer F344 rats were randomly assigned to one of the following four treatments for 14 days: G0 (control diet), G2.5 (control diet + 2.5% of dextrin), G5 (control diet + 5% of dextrin), and G10 (control diet + 10% of dextrin). After 14 days, total cecal weight, cecal content, and cecal wall weight were significantly increased in G5 and G10 compared to G0. At the same time, cecal pH was significantly lower in G10 compared to G0. Total SCFA concentration was significantly higher in G10 than in G5, G2.5, and G0, and significantly higher in G5 than in G0. Acetate, butyrate, and propionate concentrations were significantly increased in G5 and G10 compared to the controls. In a second trial based on a similar design, eighteen male Fischer F344 rats were treated with a control diet supplemented with 5% of dextrin or 5% of fructo-oligosaccharide. The results obtained with NUTRIOSE® were similar to those obtained with the fructo-oligosaccharide. In a third experiment, two groups of 5 Fischer F344 rats were orally treated with 100 and 1,000 mg/kg NUTRIOSE®, respectively, and from 18% to 25% of the dextrin was excreted in the feces. The results of these three studies show that the consumption of NUTRIOSE®, by its effects on total cecal weight, cecal content, cecal wall weight, pH, and SCFA production, could induce healthy benefits since these effects are reported to be prebiotic effects.